2020
DOI: 10.1371/journal.pone.0229357
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of health care resource utilization among preterm and term infants hospitalized with Human Respiratory Syncytial Virus infections: A systematic review and meta-analysis of retrospective cohort studies

Abstract: Introduction Data on the variation in the medical resource utilization rate of Human Respiratory Syncytial Virus (HRSV) infected children by gestational age have recently been made available. This review aimed to determine whether prematurity is independently associated with the use of medical resources in hospitalized children for HRSV infections. Methods We conducted this systematic review on cohort studies published on the medical resources use in preterm and full-term patients hospitalized for confirmed HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Respiratory syncytial virus (RSV) is one of the main etiological agents of infections affecting the lower respiratory tract among infants and children under five years of age, and it accounts for nearly 75% of bronchiolitis and 40% of pneumonia cases in infants up to one year of age during the RSV season 1,2 . Usually, the first infection progresses as an ordinary cold; however, severe RSV infections are responsible for hospitalization and, eventually, the need of mechanical ventilation (MV), mostly in children of less than 1 year of age 1,3 .…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory syncytial virus (RSV) is one of the main etiological agents of infections affecting the lower respiratory tract among infants and children under five years of age, and it accounts for nearly 75% of bronchiolitis and 40% of pneumonia cases in infants up to one year of age during the RSV season 1,2 . Usually, the first infection progresses as an ordinary cold; however, severe RSV infections are responsible for hospitalization and, eventually, the need of mechanical ventilation (MV), mostly in children of less than 1 year of age 1,3 .…”
Section: Introductionmentioning
confidence: 99%
“…RSV is a seasonal common respiratory virus and a leading cause of morbidity and hospitalization in the paediatric population. (6) When comparing health resource utilisation among preterm and term infants hospitalised with RSV, a systematic review by Kenmoe et al (2020) (7) concluded that irrespective of gestation, preterm infants have poorer outcomes and greater utilisation of health resources than term infants.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its acute onset, rapid progress and severe illness, the Ministry of Health of our country divides it into 1 of the 4 major pediatric diseases, and it is also listed as 1 of the 3 important global childhood diseases by World Health Organization. [ 7 ] The studies have shown that most of the pneumonia in infants and children, especially those within 6 months, is caused by a virus infection, and the most common pathogens are RSV, influenza virus, adenovirus, and so on. The infection caused by RSV is the first.…”
Section: Introductionmentioning
confidence: 99%